Naučni, politički i historijski značaj trotomnog djela Dejtonski (mirovni) sporazum / Scientific, Political and Historical Importance of three-volume Pus Dayton (Peace) Agreement: Legalizacija genocida u Republici Bosni i Hercegovini / Legalization of Genocide in Republic Bosnia and Herzegovina - Ramić, Emir (Pregled: časopis za društvena pitanja / Periodical for social issues, 2018)
Review of a book Dayton (Peace) Agreement – Legalization of Genocide in Republic Bosnia and Herzegovina by Academician Prof. Dr. Smail Ĉekić (Sarajevo: Institute for Research of Crimes Against Humanity and International Law of the University of Sarajevo, 2016).